Juridical Analysis of The Spread of Hate Speech Conducted by Responsible Parties Through Social Media - Nova Konny Umboh; Hudi Yusuf (International Journal Labs, 2023)
Convenience freedom argues with dependence on technology brings the development of new types of crime that as appearance speech hatred or hate speech that is done on social media either from typing as well as videos. such things, if not arranged more continue so, would be very worrying, society will not be off bounds and will raise inconvenience or feeling offended at someone or a group certain. The article will discuss How law criminals looked at criminal speech hatred or this hate speech and will also discuss what is the proof system in following criminal speech hatred. The method used to study which normative law is enforced with the method of researching material libraries and approaches used is approach related legislation with follow criminal speech hate. Results and discussion obtained If We see in the Criminal Code and regulations other legislation already explained several articles that can be imposed on someone who does speech hatred or hate speech. Articles that regulate action about Speech Hatred to a person, a group, or institution based on a Circular Letter National Police Chief No: SE/06/X/2015 contained inside Article 156, Article 157, Article 310, Article 311, then Article 28jis. Article 45 paragraph (2) of Law Number 19 of 2016 concerning information and transactions electronics and Article 16 of Law No. 40 of 2016 concerning deletion of Racial and Ethnic Discrimination. and proof that was made For inspect follow criminal speech hatred This is still based on with tools arranged evidence in the Criminal Code.